Peran Masjid Lautze 2 Bandung dalam Dakwah dan Budaya - Mila Mardotillah; Amin Hendro; Rini Soemarwoto; Ardini Raksanagara (Khazanah Theologia, 2020)
Moslem is a human obedience in submission to Allah SWT. The surrender to Allah SWT consists of spiritual and civic practices based on the Quran and Sahih Hadits. In community practices are influenced by how culture forms in society. Identity is part of the culture and social environment that can be shifted according to the dynamics of society life. Identity revolves around the space and time of every generation in the world of everyday life that comes from human thoughts and actions and evolves into real practice including Chinese culture which became a variety of Nusantara ethnic groups summarized in the activities of the Lautze 2 Mosque.Â  The aim of this article is to examine how a Chinese Muslim as an Indonesian Nation by maintaining Chinese cultural identity without conflicting with religious rules by making the mosque utilizes. The method used is descriptive qualitative method to analyze how the Lautze 2 Mosque in Bandung has an active role in community activities and daâ€™wah. The result show that the Chinese Muslim community has an active role in the utilize of the Lautze 2 Mosque as a means of religious da'wah, has an active role in helping people regardless of ethnicity and customs but still maintaining their identity as Chinese Muslims.